Radical Act and Political Withdrawal in Han Kang’s The Vegetarian - Sulistya Ningtyas (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2022)
The multi-interpreted narrative of Han Kang’s novel The Vegetarian is developed on an allegory. In this study, the allegory is seen as the meaning of freedom where the subject chooses to resist social intervention through the radical Act and political withdrawal — two main practices of action in the Žižek study. This study aims to examine the practices of action demonstrated by the protagonist that resulted from her childhood trauma. By applying Žižek’s theory of radical politics, the results of the study revealed the radical Act of being a vegetarian taken by the main character as her criticism of the violent environment. Further, the subject’s political withdrawal from living as a normal human indicates that she has gone beyond the radical Act. Even though the subject collapses in her effort to transform to become a tree, her courage to start taking this action in the first place confirms that she has value as an authentic subject.Keywords: vegetarian; trauma; Žižek study; radical Act; political withdrawal; The Vegetarian